Do owners recognise abnormal equine behaviour when tacking‐up and mounting? A comparison between responses to a questionnaire and real‐time observations. (23rd March 2021) - Dyson, S.; Bondi, A.; Routh, J.; Pollard, D.; Preston, T.; McConnell, C.; Kydd, J.
Summary: Background: Causes of abnormal behaviour during tacking‐up or mounting are multifactorial, but may be associated with an ill‐fitting saddle, a rider sitting on the caudal third of the saddle, or lameness. Objectives: To determine whether: (1) owners believed their horse showed abnormal behaviour when tacked‐up or mounted; (2) this agreed with observations by a veterinarian. Study design: Cross‐sectional study; convenience sample. Methods: Horses were undergoing prepurchase examinations, investigation of poor performance, or were recruited by invitation. Owners were asked if their horse showed abnormal behaviour when tacked‐up or mounted and subsequently whether they showed specific behaviours (yes/no) during bridling, saddling, girthing and mounting. Each horse was observed during tacking‐up and mounting by one veterinarian who recorded the occurrence of each behaviour. Agreement between the owners and the veterinarian was evaluated using intraclass correlation (ICC) coefficients with 95% confidence intervals (CI). Results: Overall 34.2% (66/193) of owners reported that their horse showed behavioural abnormalities during tacking‐up or mounting. There was poor to good agreement between the owners and veterinarian for horses putting their head up to avoid bridling (ICC 0.53, CI 0.37, 0.64) and being reluctant to open their mouth for the bit (ICC 0.52, CI 0.36, 0.64). There was poor to fair agreement for evading noseband tightening (ICC 0.41, CI 0.21, 0.56), elevating the head (ICC 0.24, CI 0.00, 0.43) and teeth grinding (ICC 0.23, CI 0.00, 0.42). For attempts to bite, there was fair to excellent agreement during saddling (ICC 0.67, CI 0.56, 0.75) and good to excellent agreement during girthing (ICC 0.73, CI 0.64, 0.79). Results for some behaviours suggested potential systematic disagreement between the veterinarian and owners. Main limitations: Potential bias of volunteers recruited by invitation. Day‐to‐day variation of behaviours is unknown. Conclusions: The majority of owners were unaware that their horses showed behavioural abnormalities during tacking‐up or mounting.